Physical and chemical properties of pomegranate fruits accessions from Kurdistan region, Iraq - Saadatian, Mohammad; ahmad, Paiza; saeed, Kanar; yunes, Pershang; ahmad, Hewen; muhammad, silaw (Journal of Agricultural Sciences (Belgrade), 2019)
The objective was to evaluate physical and chemical properties of ten pomegranate accessions collected from different district in Kurdistan regional, Iraq. Accessions showed variability in all of traits except total phenolic and antioxidant capacity. Considerable variation in the characteristics studied was found and valuable pomological traits were observed. Cluster analysis produced cases of homonym between some accessions. Principle component analysis showed that the component explaining the greatest variability positively correlated with fruit weight, total aril weight, total peel weight, volume of juice, total aril weight, total soluble solids (TSS), fruit length, fruit diameter, total peel weight, pH, aril length, and 100 seed fresh weight but negatively correlated with titratable acidity (TA). Fruit weight was positively correlated with total aril weight, total peel weight, volume of juice, TSS, aril length, 100 seed fresh weight, fruit length and fruit diameter. Volume of juice was correlated with TSS, aril length, 100 seed fresh weight, fruit length, fruit diameter that may be large fruit in size be better for juice extraction process. No correlation was found between total phenolic compounds and antioxidant capacity. The associations found among physical and chemical traits suggest that consumers should use large fruit with large aril so that they have more juice in pomegranates. So ‘Choman’, ‘Raniyeh’ and ‘Halabja’ cultivars were more juice other than.
Keywords: weights; property; Pomegranates; Length; fruits; correlations; Chemicals; chemical properties